Hematology Laboratory Abnormalities in Patients with Coronavirus Disease 2019 (COVID-19) - Christensen, Bianca (Semin Thromb Hemost, 2020)
Over the past few months, Coronavirus Disease 2019 (COVID-19) has spread across much of the world leading to a pandemic. Many infected individuals do not experience signs or symptoms, or experience only mild symptoms, whilst a subset experience severe disease, which is often fatal. A number of laboratory tests have been found to be abnormal in hospitalized patients, and some studies suggest some of these tests can predict an unfavorable outcome. These include markers of acute phase reaction (elevated C-reactive protein, erythrocyte sedimentation rate, white blood cell count, fibrinogen, procalcitonin, factor VIII, von Willebrand factor), signs of tissue injury (elevated lactic dehydrogenase, alanine aminotransferase, cardiac troponins), changes in hemostasis and coagulation (elevated D-dimer, prolonged prothrombin time, decreased platelets, decreased antithrombin, elevated factor VIII and von Willebrand factor), and decreased lymphocytes. Additional studies are needed to confirm the most ideal panel of tests, and to confirm the efficiency of laboratory tests to predict clinical outcome, as well as the ideal anticoagulation management.